Antibiotic prescribing practices, perceived constraints, and views on antimicrobial resistance among general and orthopedic surgeons in central India - Kristina Skender; Anna Machowska; Shweta Khare; Vivek Singh; Cecilia Stålsby Lundborg; Megha Sharma (Scientific Reports)
Abstract India has one of the world’s highest burdens of antimicrobial resistance (AMR). Broad-spectrum antibiotics are routinely and empirically initiated in surgery and orthopedic departments, contributing to the AMR. This study aimed to explore the capabilities, opportunities and motivation that influence antibiotic prescribing practices of general and orthopedic surgeons in Central India. This qualitative study was guided by the Capability, Opportunity, Motivation-Behavior model (COM-B) and the Theoretical Domains Framework (TDF). Semi-structured interviews were conducted until redundancy was achieved, including 15 general and orthopedic surgeons in three private-sector hospitals in Ujjain district. Questions were formulated to explore how decisions about antibiotic prescribing are made, and surgeons´ perceptions of antibiotic use, AMR and potential solutions. Manifest and latent content analysis was used. Three main themes were revealed: (1) Antibiotic prescribing decision is a multifactorial process influenced by environmental and sociocultural factors; (2) Infection prevention and control (IPC), diagnostics and treatment need strengthening; (3) AMR is a social problem that requires a collective effort. Participants emphasized the critical role of environmental (e.g., dusty rural setting) and sociocultural factors (e.g., patients’ socioeconomic status) in influencing antibiotic prescribing decisions. Prescribing practices were mostly empirical and varied between participants. Junior practitioners expressed a strong desire for regulation, guidelines, feedback and improvement, whereas senior practitioners were more confident in their prescribing. Doctors expressed frustration and hopelessness when treating resistant infections and recalled the significant contribution of the COVID-19 pandemic to inappropriate antibiotic use. The AMR problem in India was perceived as a broader social issue requiring collective action. Proposed solutions included strengthening IPC and diagnostic practices, developing contextualized antibiotic prescribing guidelines, stricter regulations on antibiotic use, and public education. Antibiotic prescribing decisions are multifactorial and context-specific, strongly impacted by prescribers’ experiences and environmental and sociocultural factors. Our findings could inform future interventions to improve antibiotic use in Central India and beyond.